Prediction of the burst pressure for defective pipelines using different semi-empirical models - Sandip Budhe; S. de Barros; M. D. Banea (Fracture and Structural Integrity)
The main aim of this work is to predict the theoretical burst pressure of defective pipelines using different semi-empirical models and compare them with the results of the hydrostatic tests. A methodology was formulated with accounting for a minimum thickness (weakest section of the pipe) over the length of the pipe to predict the most conservative burst pressure. With a simple analytical expression, a reasonable accuracy and more conservative burst pressure can be obtained for any arbitrary defect shapes. A variation of burst pressure was found between theoretical prediction and hydrostatic burst test results with respect to the different semi-empirical models even for the same corroded defects. Different defect geometry shapes and pipe material conditions are the possible causes for variation in the burst pressure between the semi-empirical models, so a careful selection of these parameters is necessary. The proposed methodology predicted a more conservative burst pressure for all arbitrary defects shapes and can predict reasonably accurate values if it accounts for the axial stress.